Effect of industrial processing for obtaining guava paste on the antioxidant compounds of guava (Psidium guajava I.) Paluma' cv. - Wolf Tasca Del'Arco, Ana Paula [UNESP]; Sylos, Celia Maria de [UNESP] (Soc Brasileira Fruticultura, 2018)
Some foods constituents are subject to change during thermal and/or industrial processing. In the fruit processing industry, guava pulp is used during guava off season to obtain guava paste, produced with the addition of sugar and citric acid, subjected to various thermal processes. This study evaluated the effect of industrial processing to obtain guava paste on the content of ascorbic acid, total carotenoids, total phenolic and total flavonoid present in guava 'Paluma' cv. The results showed that there was an increase of antioxidants in guava pulp (15% ascorbic acid, 59% total carotenoids, 8% total phenolics and 54.5% total flavonoids), probably due to their increased concentration as a result of water loss during processing. There was a reduction in the contents of antioxidants compounds in guava paste (42, 13, 31 and 6.5% respectively). The antioxidant capacity was evaluated by the DPPH method, and the results showed that guava 'Paluma' cv. and its byproducts have an important antioxidant capacity, with moderate positive correlation among guava anti-radical DPPH center dot activity with the contents of acid ascorbic, carotenoids and phenolics and, for the guava paste anti-radical DPPH center dot activity, there was very high positive correlation with the content of carotenoids and high positive correlation with total content of phenolic compounds.
Keywords: Ascorbic Acid; Carotenoids; Phenolics; Antioxidant Activity